Zakat and tax reporting: Disclosures practices of Shariah compliance companies - Nik Mohd Norfadzilah, Nik Mohd Rashid (2011)
The aspects of transparency and clear in muamalah contracts are vital in any form of business activities in complying with Shariah principles. The element of "gharar " or unknown and uncertainty are totally not permissible by the Shariah as its caused injustice to social economics. The Al-Quran has clearly forbidden business transactions that caused injustice to the society. Zakat which is based on the principle of purifying and growth is an important aspect in Islamic economic. Zakat on business income which is calculated based on growth or net working capital models is a compulsory obligation for Shariah companies. The issue of MASB technical release i–1 accounting for zakat on business and the announcement of Shariah-compliance companies by the Securities Commission Malaysia recently had initiated the current study to explore the zakat reporting compliance among the Shariah-compliance companies. Further, the development of Islamic finance and capital market requires policymakers, practitioners and zakat scholars to look into the clear standards and policy on zakat to be imposed on the Shariah-compliance companies